Digital Transformation in the Hospitality Industry: Improving Efficiency and Guest Experience - Amirulloh Anwar, Fahmi; Deliana, Dian; Suyamto, Suyamto (International Journal of Management Science and Information Technology, 2024)
Digital transformation in the hospitality industry has become critical in improving operational efficiency and guest experience. This study aims to analyze the impact of implementing digital technologies, such as Artificial Intelligence (AI), the Internet of Things (IoT), and big data analytics, on operational performance and guest satisfaction in star-rated hotels in Indonesia. Using a qualitative descriptive approach, this study was conducted through in-depth interviews with operational and IT managers from five-star-rated hotels in Jakarta and Bali, which have adopted digital technologies in their operational activities. The results showed that implementing a cloud-based property management system can increase operational efficiency by up to 30%. In comparison, using AI, such as chatbots, can reduce staff workload by up to 70%. The use of big data analytics also allows hotels to provide more personalized services, increasing guest satisfaction by up to 15%. The study also found that contactless digital technologies, which have become increasingly important during the COVID-19 pandemic, improve guests’ perceptions of safety and comfort. However, system integration, staff training, and initial investment costs are the main challenges faced. The study concluded that digital transformation significantly improves hotel efficiency, guest satisfaction, and competitiveness in an increasingly competitive market. Continuous adoption of digital technologies is highly recommended to maintain the relevance of the hospitality industry in the future.